The productivity of polymorphic stream equations and the composition of circular traversals - Balestrieri, Florent (2015)
This thesis has two independent parts concerned with different aspects of laziness in functional programs. The first part is a theoretical study of productivity for very restricted stream programs. In the second part we define a programming abstraction over a recursive pattern for defining circular traversals modularly.